Homework Help

If x/(b+c-a)=y/(c+a-b)=z/(a+b-c);prove that x(by+cz-ax)=y(cz+ax-by)=z(ax+by-cz)  

user profile pic

topperoo | Student, Grade 10 | (Level 1) Salutatorian

Posted May 24, 2012 at 12:37 PM via web

dislike 2 like

If x/(b+c-a)=y/(c+a-b)=z/(a+b-c);prove that

x(by+cz-ax)=y(cz+ax-by)=z(ax+by-cz)

 

1 Answer | Add Yours

Top Answer

user profile pic

thilina-g | College Teacher | (Level 1) Educator

Posted May 24, 2012 at 1:08 PM (Answer #1)

dislike 2 like

If, `x/(b+c-a)=y/(c+a-b) =z/(a+b-c)`

Then,

`(b+c-a)/x=(c+a-b)y=(a+b-c)/z = k`

Then,

`b+c-a = kx`

`c+a-b = ky`

`a+b-c = kz`

 

This gives,

`c = k/2(x+y)`

`b = k/2(x+z)`

`a = k/2(y+z)`

 

Multiplying above three equations by z,y and x respectively.

`cz = k/2(x+y)z`

`by = k/2(x+z)y`

`ax = k/2(y+z)x`

 

Let `k/2 = 1/p` , then,

 

Rearranging gives,

`xz+yz = pcz`

`xy+yz = pby`

`xy+xz = pax`

 

Therefore,

`pby+pcz-pax = xy+yz+xz+yz-xy-xz`

`pby+pcz-pax = yz`

`by+cz-ax = (yz)/p`

Therefore, multiplying by x on both sides,

`x(by+cz-ax) = (xyz)/p`

Similarly, you can get.

`y(cz+ax-by) = (xyz)/p`

`z(ax+by-cz) = (xyz)/p`

 

Therefore, by combining above three,

`x(by+cz-ax) =y(cz+ax-by) =z(ax+by-cz) =(xyz)/p`

 

Therefore,

`x(by+cz-ax) =y(cz+ax-by) =z(ax+by-cz) `

 

pby+pcz-pax =

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes